Taxonomy of Individual Variations in Aesthetic Responses to Fractal Patterns - Spehar, Branka; Walker, Nicholas; Taylor, Richard P. (Frontiers in Human Neuroscience, 2016)
In two experiments we investigate group and individual preferences in a range of different types of patterns with varying fractal-like scaling characteristics. In Experiment 1 we used 1/f filtered grayscale images as well as their thresholded (black and white) and edges only counterparts. Separate groups of observers viewed different types of images varying in slope of their amplitude spectra. Although with each image type, the groups exhibited the “universal” pattern of preference for intermediate amplitude spectrum slopes, we identified 4 distinct sub-groups in each case. Sub-group 1 exhibited a typical peak preference for intermediate amplitude spectrum slopes (‘intermediate’; approx. 50%); sub-group 2 exhibited a linear increase in preference with increasing amplitude spectrum slope (“smooth”; approx. 20%), while sub-group 3 exhibited a linear decrease in preference as a function of the amplitude spectrum slope (“sharp”; approx. 20%). Sub-group 4 revealed no significant preference (“other”; approx. 10%). In Experiment 2, we extended the range of different image types and investigated preferences within the same observers. We replicate the results of our first experiment and show that individual participants exhibit stable patterns of preference across a wide range of image types. In both experiments, Q-mode factor analysis identified two principal factors that were able to explain more than 80% of inter individual variations in preference across all types of images, suggesting a highly similar dimensional structure of inter individual variations in preference for fractal-like scaling characteristics.